Papillon-Lefèvre Syndrome: Diagnosis, Dental Management, and a Case Report - Jean-Claude Abou Chedid; Michel Salameh; Abbass El-Outa; Ziad E. F. Noujeim (Case Reports in Dentistry)
Aim. This paper revisits Papillon-Lefèvre syndrome (PLS), addresses its diagnostic update and dental management, and reports a case of a 5-year-old Lebanese patient with consanguineously married parents. Background. PLS, also known as “keratoris palmoplantaris with periodontopathia” and “hyperkeratosis palmoplantaris with periodontosis,” is an extremely rare autosomal-recessive trait that combines a diffuse palmoplantar hyperkeratosis and a severe generalized, progressive prepubertal form of a precocious form of juvenile, aggressive periodontitis. Case Description. We are reporting a 5-year-old boy that sustained a spontaneous loss of all his primary teeth. At consultation, he was under treatment for hyperkeratosis of his palms and soles. Detailed family history of the child revealed that the patient’s parents, grandparents, and relatives were consanguineously married and two of his cousins displayed similar clinical signs (palmoplantar hyperkeratosis and premature loss of deciduous and most of the permanent teeth). Conclusion. PLS is an extremely rare disorder that usually becomes apparent from approximately 1-5 years of age. Genetic counseling should always be suggested to parents of affected children, informing them of chances of their offspring having the inherited disease.